Fetal autopsy and closing the gap. (24th November 2015) - Kandasamy, Yogavijayan; Kilcullen, Meegan; Watson, David
Abstract : Over the past 30 years, the perinatal mortality rate (PMR) in Australia has been reduced to almost a quarter of that observed in the 1970s. To a large extent, this decline in the PMR has been driven by a reduction in neonatal mortality. Stillbirth rates have, however, remained relatively unchanged, and stillbirth rates for Aboriginal or Torres Strait Islander mothers have remained approximately twice that for non‐Indigenous women over the last 10 years. The causes for this difference remain to be fully established. Fetal autopsy is the single most important investigative tool to determine the cause of fetal demise. While facilitators and barriers to gaining consent for autopsy have been identified in a non‐Indigenous context, these are yet to be established for Indigenous families. In order to address the gap in stillbirths between Indigenous and non‐Indigenous mothers, it is essential to identify culturally appropriate ways when approaching Aboriginal and Torres Strait Islander families for consent after fetal death. Culturally safe and appropriate counselling at this time provides the basis for respectful care to families while offering an opportunity to gain knowledge to reduce the PMR. Identifying the cause of preventable stillbirth is an important step in narrowing the disparity in stillbirth rates between Indigenous and non‐Indigenous mothers.